Transformation of Jalan Kuala Kangsar and Jalan Klebang Selatan from unsignalised to intersection - Nurulakma, Md Desa (2014)
During peak hour at study at location namely the intersection of Jalan Kuala Kangsar and Jalan Klebang Selatan we observed difficulties to the vehicles using the road due to the heavy turning in The intersection also is not in accordance with the design road standards. This will most likely result with occurrence of traffic accidents. Jalan Kuala Kangsar is the main route between the Ipoh city to Kuala Kangsar Town where Jalan Kiebang Selatan is linking to residential estet. Road standard for Jalan Kuala Kangsar is of JKR R5 and Jalan Klebang Selatan is of JKR U3. The T-intersection unsignalised intersection had been in operation over the past 10 years. The purpose of this study was to obtain road capacity and evaluating the level of services (LOS) the intersection. This study will focus on not only on the traffic study but also on the transformation of an unsignalised intersection to a signalised intersection. In this study, traffic survey data of vehicles, direction of movement and road geometry data were collected. The survey shows that the number of vehicles passing warrant through the road exceeding 1500 vehicles per hour and this for the installation of traffic lights. Noon peak hour indicated the volume of lane. Transformation of Jalan Kuala Kangsar and Jalan Klebang Selatan from unsignalised to signalised is required because the existing intersection could not accommodate the number of vehicles that pass through the intersection exceed the volume allowable at an unsignalised intersection.